IMPLEMENTASI PENYEDIAAN RUANGAN KHUSUS TERHADAP ANAK DI POLRESTA PEKANBARU - Siregar, Marito; Kadaryanto, Bagio; Harahap, Irawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
In general, children in adult prisons are at risk of experiencing trauma and other psychological problems because the prison environment is not in accordance with their developmental needs. Children placed in adult prisons can experience great mental and emotional stress. The method used is sociological legal research. Based on the results of the study, it is known that the implementation of the provision of special rooms for children at the Pekanbaru Police based on Law Number 11 of 2012 concerning the juvenile criminal justice system has not been running well, because there are still child perpetrators who are combined in adult rooms. The provision of this special room aims to ensure that children in conflict with the law receive treatment in accordance with their rights as children. This special room is designed to separate children from adult prisoners, in order to avoid negative influences that can damage the child's psychological development. Obstacles in the implementation of the provision of special rooms for children at the Pekanbaru Police based on Law Number 11 of 2012 concerning the juvenile criminal justice system are the limited facilities and infrastructure that are in accordance with the needs of children, such as separate rooms from adult detention rooms, lack of budget and facilities to build special rooms for children, and human resources related to the lack of training for officers responsible for handling children in conflict with the law. Efforts to overcome obstacles in the implementation of the provision of special rooms for children at the Pekanbaru Police based on Law Number 11 of 2012 concerning the juvenile criminal justice system are to provide a budget and allocation of resources to build facilities and infrastructure that are in the provisions of laws and regulations, more intensive coordination with related agencies, such as social institutions and local governments, to provide special rooms in accordance with legal provisions, and include improving psychological and rehabilitation facilities, so that children are not only placed in separate rooms, but also receive treatment that supports social recovery and reintegration.